Climatic signals in δ13C and δ18O of tree-rings from White Spruce in the Mackenzie Delta Region, Northern Canada - Porter, Trevor J.; Pisaric, Michael F.J.; Kokelj, Steven V.; Edwards, Thomas W.D. (Arctic, Antarctic, and Alpine Research, 2009)
This is the publisher's version of an article published by the University of Colorado at Boulder, Institute of Arctic and Alpine Research. Here we present the first tree-ring series (1850–2003) of stable carbon (δ13C) and oxygen (δ18O) isotope ratios from a high-latitude treeline site in northwestern Canada. Both δ13C and δ18O were measured at annual resolution from whole-ring α-cellulose of three white spruce trees (Picea glauca [Moench] Voss) growing in the Mackenzie Delta. There is a strong positive association between δ13C and maximum summer temperatures. This relation likely results from the influence of temperature-induced drought stress on stomatal conductance. Mean summer relative humidity is also significantly correlated, inversely, with δ13C reflecting its direct influence on stomatal conductance. The δ18O record is strongly and positively correlated with early-spring to mid-summer minimum temperatures likely owing to the temperature dependence of δ18O in precipitation and uptake of this water during the growing season. Mean summer relative humidity is also significantly and inversely correlated with δ18O due to leaf water evaporative enrichment. Our δ13C and δ18O records contain a large amount of climate-driven variability indicating their considerable potential to infer past climate changes in the Mackenzie Delta region. Financial support was provided by Indian and Northern Affairs Canada: Water Resources Division and a Natural Sciences and Engineering Research Council of Canada (NSERC) Discovery Grant to M.F.J. Pisaric.